Identification of microorganisms on mobile phones of intensive care unit health care workers and medical students in the tertiary hospital - Ivan Kotris; Domagoj Drenjančević; Jasminka Talapko; Suzana Bukovski (Medicinski glasnik, 2017)
Aim: To identify and investigate a difference between microorganisms present on intensive care unit (ICU) health care workers' (HCW, doctors, nurses or medical technicians) and medical students' mobile phones as well as to investigate a difference between the frequency and the way of cleaning mobile phones. Methods: Fifty swabs were collected from HCWs who work in the ICU (University Hospital Centre Osijek) and 60 swabs from medical students (School of Medicine, University of Osijek). Microorganisms were identified according to standard microbiological methods and biochemical tests to the genus/species level. Results: Out of 110 processed mobile phones, mobile phones microorganisms were not detected on 25 (22.7%), 15 (25%) students' and 10 (20%) HCW's mobile phones. No statistically significant difference was found between the number of isolated bacteria between the HCW' and students' mobile phones (p>0.05). Statistically significant difference was found between both HCW and students and frequency of cleaning their mobile phones (p<0.001). A significant difference was also obtained with the way of cleaning mobile phones between HCWs and students (p <0.001). Conclusion: The most common isolated microorganisms in both groups were coagulase-negative staphylococci (CoNS) and Staphylococcus aureus. Most HCWs cleaned their mobile phones at least once a week, 35 (52.0%), and most medical students several times per year, 20 (33.3%). HCW clean their mobile phones with alcohol disinfectant in 26 (40.0%) and medical students with dry cloth in 20 (33.3%) cases.
Keywords: cell phones; swab; coagulase-negative staphylococci